Formulation Development of Rotigotine Transdermal System Using Dot-Matrix Technology (International Journal of Pharmaceutical Sciences and Drug Research, 2020)
The purpose of this research was to prepare and evaluate drug-in-adhesive type patches of rotigotine using dot-matrix technology, which is the new generation of drug-in-adhesive transdermal delivery system (TDS) that deliver drug therapy through less patch surface area and without compromising adhesion. Preformulation studies, like solubility in permeation enhancers, compatibility study, transmission study, uptake study, and crystallization study of rotigotine in various pressure-sensitive adhesive (PSA) polymers were performed. Transdermal system was prepared by solvent casting method. Central composite design (CCD) was chosen for optimization of the formulation. Design of experiment (DoE) was used to study the impact of critical formulation parameters, like silicone adhesive concentration, povidone K29/32 concentration, and propylene glycol concentration. Crystallization study of rotigotine in different PSAs suggested that crystal inhibitor is required to load drugs above 5%. Selection of optimum batch was made using a constraint-based graphical optimization technique. The optimum batch exhibited desired in vitro adhesion parameters, like peel, tack, shear, and permeation rate, which is suitable for 3 days’ wear properties and desired permeation rate. The optimum batch was evaluated for appearance, weight of matrix, thickness, % assay of drug content, in vitro adhesion testing, cold flow study, and ex vivo skin permeation studies. Backing film Scotchpak 9730 and release liner Scotchpak-1022 was selected based on transmission and uptake study of rotigotine. Stability study indicates that developed formulation remains stable. The present research confirms the feasibility of developing rotigotine transdermal system using novel technology.